Análisis de los estándares de organización de la empresa MC SERVICES para automatización de funciones laborales - Cevallos Romero, John Mauricio (2021)
Technology is spreading more and more in the business world, where companies are implementing it in their organization with the aim of not being left behind in the face of competition. For this reason, it is very important to be clear about the strategic evolution that a company is going to have in organizational terms. The content of this case study aims to create an organization design to automate processes in the company "MC SERVICES", which is a developing company whose activities are maintenance and repair of electrical appliances. The analysis of the measurement of automation of the processes will facilitate the organization to serve as support, for the improvement of its activities in the achievement of its systematization and to optimize the management of resources. The technological dimension of the organization has a significant impact, especially due to the update itself. A software development area must be taken into account in it. The company must analyze several factors that may negatively impact mainly due to additional costs that process automation can generate.